Raz jeszcze o literaturze i muzyce - Walczak, Jakub (Przestrzenie Teorii, 2019)
The article deals with the still relevant interdisciplinary research movement, which chose the relation between music and literature as the object of its analysis. The book by Libor Martinek and Małgorzata Gamrat, which is the result of cooperation between a literary scholar and a musicologist, is the main basis for and contribution to this discussion. Following the path set by P. Scher, these authors have found a methodological dimension, on which issues of literary text functioning in the music sphere are located, and on the other hand, attempts to define a so-called literary text’s musical aspects.